2020
DOI: 10.2147/nsa.s287658
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Bioactivity of Silver Nanoparticles: Antibacterial Properties, Influence on Copper Status in Mice, and Whole-Body Turnover

Abstract: The ability of silver nanoparticles (AgNPs) of different sizes to influence copper metabolism in mice is assessed. Materials and Methods: AgNPs with diameters of 10, 20, and 75 nm were fabricated through a chemical reduction of silver nitrate and characterized by UV/Vis spectrometry, transmission and scanning electronic microscopy, and laser diffractometry. To test their bioactivity, Escherichia coli cells, cultured A549 cells, and C57Bl/6 mice were used. The antibacterial activity of AgNPs was determined by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 92 publications
5
35
0
1
Order By: Relevance
“…Overall, the zones of growth inhibition reflect the size dependent antimicrobial activity of TCE-Ag NPs against both bacterial as well as fungal strains. Our findings on the size and dose dependent antibacterial activity of TCE-Ag NPs are consistent with previously published research [ 53 , 54 ]. According to the recent work by [ 10 , 55 , 56 ], AgNPs synthesized by various methods have also antimicrobial action against Gram-negative and Gram-positive bacteria, as well as yeast, C. albicans .…”
Section: Resultssupporting
confidence: 93%
“…Overall, the zones of growth inhibition reflect the size dependent antimicrobial activity of TCE-Ag NPs against both bacterial as well as fungal strains. Our findings on the size and dose dependent antibacterial activity of TCE-Ag NPs are consistent with previously published research [ 53 , 54 ]. According to the recent work by [ 10 , 55 , 56 ], AgNPs synthesized by various methods have also antimicrobial action against Gram-negative and Gram-positive bacteria, as well as yeast, C. albicans .…”
Section: Resultssupporting
confidence: 93%
“… 50 , 51 AgNPs trigger an increase in intracellular ROS, and reactive hydroxyl radicals damage DNA, which results in cell death. 52 AgNPs coated with plant bioconstitutents induce oxidative stress, leading to apoptosis via caspase-mediated and mitochondria-dependent pathways. 53 , 54 Nanoparticles induce hydroxyl radical formation and are highly toxic to cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…50,51 AgNPs trigger an increase in intracellular ROS, and reactive hydroxyl radicals damage DNA, which results in cell death. 52 AgNPs coated with plant bioconstitutents induce Figure 10 Morphological alterations in (A) TERT4 cell line and (B) A 549 cell lines exposed to AME-AgNPs at 1-100 mg/mL for 24 h. Images were taken using phase contrast inverted microscope at 20x magnification. oxidative stress, leading to apoptosis via caspase-mediated and mitochondria-dependent pathways.…”
Section: Mtt Assaymentioning
confidence: 99%
“…As far as size and shape are concerned, particles of a smaller size with good monodispersal of AgNPs seem to be more effective and have superior properties [18]. Many previous studies have indicated that the bactericidal properties of nanoparticles are size-dependent [7,[40][41][42]. The researchers have identified that AgNPs act primarily in three possible mechanisms against Gram-negative bacteria: (1) nanoparticles (mainly in the range of 1-10 nm) attach to the surface of the cell membrane, cause permeability and disrupt the respiration in bacteria; (2) AgNPs penetrate inside the bacterial cell and cause serious damage by interacting with sulfur-and phosphorus-containing macromolecules; (3) AgNPs release silver ions, which contribute to the bactericidal effect of the AgNPs [38,43].…”
Section: Discussionmentioning
confidence: 99%